Pharmacological targeting of chemokine (C-X-C motif) receptor 4 in porcine polytrauma and hemorrhage models - Bach, Harold H. (J Trauma Acute Care Surg, 2016)
BACKGROUND: Recent evidence suggests that chemokine receptor CXCR4 regulates vascular α(1)-adrenergic receptor function and that the noncognate CXCR4 agonist ubiquitin has therapeutic potential after trauma/hemorrhage. Pharmacologic properties of ubiquitin in large animal trauma models, however, are poorly characterized. Thus, the aims of the present study were to determine the effects of CXCR4 modulation on resuscitation requirements after polytrauma, to assess whether ubiquitin influences survival times after lethal polytrauma-hemorrhage, and to characterize its dose-effect profile in porcine models. METHODS: Anesthetized pigs underwent polytrauma (PT, femur fractures/lung contusion) alone (Series 1) or PT/hemorrhage (PT/H) to a mean arterial blood pressure of 30 mmHg with subsequent fluid resuscitation (Series 2 and 3) or 40% blood volume hemorrhage within 15 minutes followed by 2.5% blood volume hemorrhage every 15 minutes without fluid resuscitation (Series 4). In Series 1, ubiquitin (175 and 350 nmol/kg), AMD3100 (CXCR4 antagonist, 350 nmol/kg), or vehicle treatment 60 minutes after PT was performed. In Series 2, ubiquitin (175, 875, and 1,750 nmol/kg) or vehicle treatment 60 minutes after PT/H was performed. In Series 3, ubiquitin (175 and 875 nmol/kg) or vehicle treatment at 60 and 180 minutes after PT/H was performed. In Series 4, ubiquitin (875 nmol/kg) or vehicle treatment 30 minutes after hemorrhage was performed. RESULTS: In Series 1, resuscitation fluid requirements were significantly reduced by 40% with 350-nmol/kg ubiquitin and increased by 25% with AMD3100. In Series 2, median survival time was 190 minutes with vehicle, 260 minutes with 175-nmol/kg ubiquitin, and longer than 420 minutes with 875-nmol/kg and 1,750-nmol/kg ubiquitin (p < 0.05 vs. vehicle). In Series 3, median survival time was 288 minutes with vehicle and 336 minutes and longer than 420 minutes (p < 0.05 vs. vehicle) with 175-nmol/kg and 875-nmol/kg ubiquitin, respectively. In Series 4, median survival time was 147.5 minutes and 150 minutes with vehicle and ubiquitin, respectively (p > 0.05). CONCLUSION: These findings further suggest CXCR4 as a drug target after PT/H. Ubiquitin treatment reduces resuscitation fluid requirements and provides survival benefits after PT/H. The pharmacological effects of ubiquitin treatment occur dose dependently.